Cross-cultural adaptation of the Heart Disease Knowledge Questionnaire: a methodological study - Lima, Fernanda Maria Alves; Jamas, Milena Temer; Meneguin, Silmara; de Avila, Maria Andreia Garcia (Escola de Enfoermagem Aurora de Afonso Costa, 2021)
Objective: to describe the process of cross-cultural adaptation to Brazilian Portuguese for the Heart Disease Knowledge Questionnaire. Method: a methodological cross-cultural adaptation study carried out between August and December 2019, in five stages: initial translation, synthesis of the translations, back-translation, evaluation by judges, and pre-test. The translated questionnaire was evaluated by a committee of nine judges regarding semantic, idiomatic, conceptual and cultural equivalences. The pre-test version was applied to 50 participants to verify understanding and clarity of the questionnaire. Results: the terms used in the different translations were reviewed, looking for those with similar meanings. Thirteen items presented an agreement percentage below 90% in the judges' assessment, with suggested changes being made. The participants in the pre-test version evaluated the questionnaire and suggested changes in eight items for better understanding. Conclusion: the Portuguese version of the Heart Disease Knowledge Questionnaire was culturally adapted for the population under study, without losing the objective of the original questionnaire.
Adaptación transcultural del Heart Disease Knowledge Questionnaire: estudio metodológico
Adaptação transcultural do Heart Disease Knowledge Questionnaire: estudo metodológico
Keywords: Cardiovascular Diseases; Conhecimento; Conocimiento; Doenças Cardiovasculares; Educación en Salud; Education in Health; Educação em Saúde; Encuestas y Cuestionários; Enfermedades Cardiovasculares; Inquéritos e Questionários; Knowledge; Surveys and Questionnaires; Traducción; Tradução; Translation